Peran Akun Tik Tok @Mojokerto Jalan-Jalan Dalam Pemasaran Pariwisata di Mojokerto - Muhamad Misbahul Irsad; Masnia Ningsih; Ratnaningrum Zusyana Dewi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Tik Tok is a very popular social media, especially in terms of marketing, education and social campaigns. Marketing via Tik Tok in creative terms has a tremendous impact on users. One of the Tik Tok users of the @Mojokerto account goes for a walk using creative videos in tourism marketing in Mojokerto. This research aims to find out how the Tik Tok @Mojokerto account works in marketing tourism in Mojokerto. This research uses a descriptive qualitative method with a content analysis approach according to Klaus Krippendorff and uses content analysis theory, tourism theory and message theory. The results of the findings of this research can be concluded that the Tik Tok account @Mojokerto provides marketing via video by conveying informative and persuasive messages related to tourism with effective and easy to understand message delivery so that the audience can give Likes, Comments, Shares. Thus, the role of the Tik Tok @Mojokerto traveling account in increasing visitors to tourism in Mojokerto can be seen as a result of effective promotion through social media platforms such as TikTok.